1988
DOI: 10.1016/0169-5150(88)90023-0
|View full text |Cite
|
Sign up to set email alerts
|

Household food demand in Burkina Faso: Implications for food policy

Abstract: Savadogo, K. and Brandt, J.A., 1988. Household food demand in Burkina Faso: implications for food policy. Agric. Econ., 2: 345-364.Chronic food production deficits since the early 1970s have prompted policymakers of Burkina Faso to emphasize technological research with the goal of increasing the production of the mostconsumed locally-grown cereals: sorghum, millet and maize. Meanwhile, urban consumers have been developing preferences for rice and wheat, cereals that are primarily imported. This study estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…It has been shown that the larger the household, the greater the demand and expenditures for food and the higher the tendency to substitute high-value food by low-value and basic foods (Savadogo and Brandt 1988; Deaton and Praxson 1998). Rose and Charlton (2002) also observed that food insecurity rates increased with increasing household size.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the larger the household, the greater the demand and expenditures for food and the higher the tendency to substitute high-value food by low-value and basic foods (Savadogo and Brandt 1988; Deaton and Praxson 1998). Rose and Charlton (2002) also observed that food insecurity rates increased with increasing household size.…”
Section: Discussionmentioning
confidence: 99%
“…Food commodities are aggregated into five groups: cereals (rice, maize, millet and sorghum); roots and tubers (plantains, yams, cocoyams, cassava, sweet potatoes and Irish potatoes); milk and dairy products; meat (beef, pork, lamb and mutton, and chicken); and fish. Savadogo and Brandt (1988) used a similar commodity classification except that they included vegetables in a separate category and rice as a separate category of imported cereals. Blanciforty and Green (1983) merged fish into the meat group and included fruits and vegetables in Downloaded by [UQ Library] at 00:23 03 November 2014 their analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Among them are the linear and dynamic linear expenditure systems (Rogers and Lowdermilk, 1991;Sasaki and Fukagawa, 1987), the dynamic adjustment model (Tambi, 1996), the Probit and Tobit models (Alzand and Adriamanjay, 1988;Capps et al, 1988;Cheng and Capps, 1988;Epperson et al, 1988;Kwakyi et al, 1989), and the AIDS model developed by Deaton and Muellbauer (1980) and employed by Blanciforty and Green (1983); Eales and Unnevehr (1988); Capps et al, (1985); Ingco (1990) and Savadogo and Brandt (1988). Of all the models, the AIDS model is particularly appealing since it is built on Stones's (1954) pioneered complete systems approach which incorporates assumptions of neoclassical demand theory and combines the best of the theoretical features of both the translog and Rotterdam models (Theil, 1978).…”
Section: Model Specificationmentioning
confidence: 99%
“…As regards the testing or imposing of the symmetry restriction, this is valid only when the theoretical price index P Ã t (equation 5) is used, and not when an approximation index (Divisia index in equation 7) is used (Deaton and Muellbauer (1980) cited in Savadago and Brandt (1988)). As the theoretical price index P Ã t is not used in this study, symmetry restrictions are neither tested nor imposed.…”
Section: The Aids Modelmentioning
confidence: 99%